Heterogeneous Photocatalysis A Solution for a Greener Earth - Lambert, Stéphanie; Mahy, Julien (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a compilation of the articles submitted in the Special Issue entitled, "Heterogeneous Photocatalysis: A Solution for a Greener Earth", from the journal Catalysts, which presents an overview of the latest advances in the development of innovative photocatalytic processes.